Ag/Au Bimetallic Nanoparticles Inhibit Tumor Growth and Prevent Metastasis in a Mouse Model - Katifelis H (Dove Medical Press, 2020)
Hector Katifelis,1 Iuliia Mukha,2 Penelope Bouziotis,3 Nadiia Vityuk,2 Charalampos Tsoukalas,3 Andreas C Lazaris,4 Anna Lyberopoulou,1 George E Theodoropoulos,5 Efstathios P Efstathopoulos,6 Maria Gazouli1,6 1Laboratory of Biology, Medical School, National and Kapodistrian University of Athens, Athens, Greece; 2Chuiko Institute of Surface Chemistry, National Academy of Sciences of Ukraine, Kyiv, Ukraine; 3Radiochemical Studies Laboratory, Institute of Nuclear & Radiological Sciences & Technology, Energy & Safety, National Center for Scientific Research “Demokritos”, Athens, Greece; 4 1st Department of Pathology, National and Kapodistrian University of Athens, Athens, Greece; 5 1st Propaedeutic University Surgery Clinic, Hippocratio General Hospital, Medical School, National and Kapodistrian University of Athens, Athens, Greece; 6 2nd Department of Radiology, Medical School, National and Kapodistrian University of Athens, Athens, GreeceCorrespondence: Maria Gazouli Email mgazouli@med.uoa.grPurpose: To evaluate the antitumor efficacy of Ag3Au1Trp1:2NPs in a SCID mouse cancer model, with respect to their effect on tumor growth, on tumor’s metastatic potential and the underlying molecular mechanism.Subjects and Methods: Ag3Au1Trp1:2NPs were radiolabeled with Gallium-68 and the biodistribution was studied in Swiss mice without tumors and in SCID mice bearing tumors. SCID mice received intratumoral Ag3Au1Trp1:2NPs and tumor size was measured using calipers. Lung and liver tissues were extracted and studied microscopically for the detection of any metastatic sites. Changes in the Caspase-3 and TNF-related apoptosis-inducing ligand (TRAIL) were also investigated using real-time PCR and Western blot techniques, respectively.Results: In the 4T1 tumor-bearing SCID mice, Ag3Au1Trp1:2NPs showed quick passive accumulation at tumor sites at 30 mins post-injection. Mice that received the highest dose of NPs (5.6mg/mL) demonstrated a 1.9-fold lower tumor volume compared to that of the control group at 11 days post-injection, while mice that did not receive NPs showed metastatic sites in liver and lung. Extracted tumor tissue of treated mice revealed increased Casp-3 mRNA levels as well as elevated TRAIL protein levels.Conclusion: Based on our results, Ag3Au1Trp1:2NPs express anti-tumor and anti-metastatic effects in vivo. Ag3Au1Trp1:2NPs also reach tumor site via the enhancement and retention effect which results in the apoptotic death of cancerous cells selectively via the extrinsic TRAIL-dependent pathway.Keywords: nanoparticles, cancer, SCID mice, TRAIL, Casp-3